FA-9 Reproductive Efficiency of Brahman Cross Cattle Using Artificial Insemination with Frozen Semen from Bali, Brahman, Limousin, and Simmental Cattle - Husnul Khotimah; Muhammad Agil; Bakti Tamba; I Ketut Karya Wisana; Sutrisnak Sutrisnak; Harianto Budi Rahardjo; Tuty L Yusuf (Hemera Zoa, 2018)
Demand and consumpsion of beef meat increases every year in Indonesia. The increase of demand is not followed by the availability supply of beef cattle production nationaly. Statistical data from Direktorat Jenderal Peternakan Indonesia showed that on the year of 2016 the demand of beef was 604.968 ton and the production of beef was only 354.770 ton. The goverment imported of beef and cattle to fulfill the lack of supply, as of 2016 there was 116.761 ton beef and 1.298.560 cattle imported to Indonesia(1).Indonesia has determined to achieve beef self–sufficiency by 2024. To achieve that goal the goverment want to increase the cattle population nationaly by requiring the cattle and buffalo farm industry to oblige the breeding programe. The goverment made some policy including Upsus SIWAB and an obligation of the feedloters of imported cattle to do breeding. According to PERMENTAN no 49 thn 2016 and it’s add on PERMENTAN no 2 thn 2017, importation of beef cattle must meet the ratio 1:5 between breeding cattle and feeder cattle.Reproductive efficiency is a parameter used to determine the success of breeding programe. Reproductive eficiency is a measure of the ability if a cow to become pregnant and produce offspring(2). Optimalization of reproductive efficiency can be one of means to increase national cattle population.Brahman Cross is one of the most common imported cattle breed to Indonesia. Husbandry and reproductive management play an important role to achieve the best result on cattle breeding programe. Feedloters who conduct breeding programe of Brahman Cross cattle (Breedlot) have the capacity and potential to increase the reproductive efficiency of their breeding programe due to they have capital and good management. Thus it is important to assess and measure the reproductive efficiency of Brahman Cross cattle artificially inseminated with frozen semen to increase the reproductive efficiency of beef cattle in the Breedlot.